UUM listed in 200th+ place in first edition, THE APAC 2017 - The Sunday Post, (Kuching) (The Sunday Post (Kuching), 2017)
ALOR SETAR: Universiti Utara Malaysia (UUM) has been listed in the top 200+ placing in the first edition of the Times Higher Education Asia- Pacific University Rankings (THE APAC) 2017 which was announced recently.